Skills for Work in Bulgaria : The Relationship between Cognitive and Socioemotional Skills and Labor Market Outcomes - World Bank (World Bank, Washington, DC, 2016)
Bulgaria is undergoing both a rapid demographic transition and a significant structural shift in its economy. Increasing longevity combined with low fertility and emigration have made Bulgaria’s age structure increasingly top-heavy and its dependency ratios higher. At the same time, the economic sectors that absorbed low-skilled workers during the high-growth early 2000s, such as construction and manufacturing, were those that contracted most during the 2008–09 economic crisis and they have not yet recovered. Meanwhile, activities demanding high-skilled labor, such as financial and business services and information, communication, and technology (ICT), have been faring relatively well. This study uses a new dataset with direct measures of cognitive and socio-emotional skills to examine the relationship between skills and labor market outcomes in Bulgaria. For a long time, labor market studies had to rely on formal educational attainment as a measure of an individual’s skills. However, the correlation between formal education and skills is not perfect, and not all diplomas are equal in terms of imparting certain skills to students. Moreover, valuable skills can be acquired without formal diplomas, for example through on-the-job training or learning-by doing. In addition to using educational attainment this study therefore looks at direct measures of two types of skills that employer’s value: cognitive skills, such as functional literacy and numeracy, and socio-emotional skills, such as self-discipline, perseverance, and ability to work well with others. The objective is to assess the extent to which these direct measures shed light on what matters for labor market success, defined as being in the labor force, being employed, and earning more. This analysis relies on original data (the Bulgarian Longitudinal Inclusive Society Survey, BLISS) collected by the World Bank and Open Society Institute–Sofia in the spring of 2013, which for the first time in the country included nationally-representative information on the cognitive and socio-emotional skills of the working-age population.